Giant axonal neuropathy: acceleration of neurofilament transport in optic axons. - Monaco, S (1985)
Giant axonal neuropathies are a group of acquired and inherited human diseases morphologically characterized by accumulation of neurofilaments (NF) in enlargements of preterminal regions of central and peripheral axons. Slow axonal transport was studied in the optic systems of rats treated with 2,5-hexanedione, a toxic compound that produces an experimental model of giant axonal neuropathy. The transport rate of NF and of two other polypeptides of Mr 64,000 and 62,000 were selectively increased. Other components of the slow axonal transport were not affected. Acceleration of labeled NF was also observed when 2,5-hexanedione was given after [35S]methionine administration. Morphometric analysis revealed that the number of NF and the axon size were decreased in regions of optic axons proximal to the enlargements. It is suggested that acceleration of NF transport leads to a longitudinal redistribution of NF: NF decrease proximally and increase distally, forming NF-containing enlargements. Evidence was obtained that polypeptides of Mr 64,000 and 62,000 are cytoskeletal components related to intermediate filaments, normally migrating with the component a of the slow axonal transport. The 2,5-hexanedione axon may provide insight into the pathogenesis of inherited and acquired giant axonal neuropathies and offers a model to investigate the relationship between number of NF and axonal size in central axons.